Sakit Kepala pada Variasi Anatomi Hidung dan Sinus Paranasal - Hakikah, Tika; Irfandy, Dolly; Budiman, Bestari Jaka (Faculty of Medicine, Universitas Andalas, 2021)
The anatomical variations of the nasal and sinus paranasal can cause headaches. The most common variants have deviated septum, concha bullosa, and agger nasi cells. These variations can cause narrowing of the osteomeatal complex. Computed tomography was the primary modality for evaluating anatomical variations of the nasal and paranasal sinuses in diagnosis and management. Functional endoscopic sinus surgery was generally performed to restore the sinuses' drainage and ventilation in anatomical variations. It has been reported a 45-year-old woman with a congested left nostril and headache that has gotten worse since 2 months ago and computed tomography of the paranasal sinuses show thickening of the bilateral maxillary sinus mucosa, bilateral anterior ethmoid, left septum deviation, concha bullous, and right inferior turbinate hypertrophy. Functional Endoscopy Sinus Surgery was performed, found anatomical variations namely, deviation septum, concha bullosa, agger nasi cells and supra agger cells. The operation gave satisfactory results. Correct evaluation of anatomical variations based on history, physical examination and investigations can assist in patient management and avoid errors during surgery. The operation gave a satisfactory result for managing symptoms on patient with anatomical variation of nasal and paranasal sinuses when compared with medicamentosa.Keywords: anatomical variations,Â agger nasi cells , concha bullosa,Â deviated septum, headache, supra agger cell